решить интеграл \int\limits {sin^{\frac{1}{3} }x cos^{-\frac{13}{3} } x } \, dx . ответ должен получиться: \frac{3}{4} tg^{\frac{4}{3} } x + \frac{3}{10} tg^{\frac{10}{3} }x + C

ulyanakovoleva ulyanakovoleva    3   27.06.2021 17:44    0

Ответы
egor911777 egor911777  27.07.2021 18:05

Пошаговое объяснение:

\int {\sin^\frac{1}{3}x\cos^{-\frac{13}{3} } } \, dx =\int {\sin^\frac{1}{3}x\cos^{-\frac{7}{3} } *} \, \cos^{-2}dx =\int {\sin^\frac{1}{3}x\cos^{-\frac{7}{3} }} \, d(\rm tg \; x) =\\\int {(\sin x\cos^{-7}x)^\frac{1}{3} } \, d(\rm tg \;x) =\int {\sqrt[3]{\frac{\sin x}{\cos^7x} } } \, d(\rm tg \; x)= \int {\sqrt[3]{\frac{\sin x}{\cos x}*\frac{1}{\cos^6x} } } \, d(\rm tg \; x)=

\int {\sqrt[3]{\rm tg \; x(\frac{1}{\cos^2x})^3 } } \, d(\rm tg \; x)=\int {\frac{1}{\cos^2x}\sqrt[3]{\rm tg \; x} } \, dx(\rm tg \; x)=\int {(1+\rm tg^2x)\rm tg^\frac{1}{3}x } \, d(\rm tg \; x)=\\\int {(\rm tg^\frac{1}{3} x+\rm tg^\frac{7}{3}x) } \, d(\rm tg \; x)=\frac{3}{4}\rm tg^\frac{4}{3}x+\frac{3}{10}\rm tg^\frac{10}{3}x+C

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика